Hyperbilirubinemia in the breastfeeding infant - Page-Goertz, Sallie; McCamman, Sarah (Sudbury, MA : Jones and Barlett, 1996)
Learn about care of the breastfeeding infant with unconjugated hyperbilirubinemia. See discussion of breastmilk and breastfeeding associated jaundice. Explore real cases and see the best approach to breastfeeding management for infants with jaundice.
Best Beginnings Productions
System Requirements : 486 (Pentium recommended), 8 MB RAM, 4X CD-ROm drive, QuickTime for windows 2.1.1
System Requirements : Macintosh : 68030 ('040 or PowerMac recommended), 8 MB RAM, 2 x CD-ROM drive (4X speed or higher recommended), QuickTime for windows 2.1.1
Keywords: Breast feeding; Hyperbilirubinemia; Infant nutrition